Covid-19 Era Learning Management in Early Childhood Education - Elfrida Agissa Kumaila; Wiwin Herwina; Imam Shofwan (Genius Journals, 2021)
The Covid-19 pandemic, which has spread throughout the world, has greatly affected human life. In starting a new normal in the sector of education, it is necessary to manage learning during the Covid-19 pandemic. This study aims to describe the learning management at PAUD Kasih Ibu during Covid-19 pandemic and supporting and inhibiting factors in the learning of Covid-19’s era. This research used qualitative research with a phenomenological approach method. There were six research subjects consisted of 1 playgroup school principal, 1 kindergarten principal, 1 playgroup teacher, 1 kindergarten teacher, and 2 representatives’ parent of PAUD Kasih Ibu’s students. The data were collected by using observation, interview, and documentation. The data validity technique used was source and method triangulation. Data analysis techniques using data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that. The implementation of the Covid-19 emergency response as a reference in learning is a supporting factor, while the inhibiting factor found is parents' busyness during SFH learning. The conclusion in this study is that the management of PAUD Kasih Ibu learning has been carried out in accordance with Permendikbud No. 137 of 2014 article 11 concerning National Standards of PAUD which consists of planning learning, implementing learning, and monitoring learning during the Covid-19 pandemic which is implemented by implementing health protocols and adapting to the situation and conditions of the area. The benefits of this research can help educators as a reference in the process towards the renewal and more developing stage of learning management during the Covid-19 era.
Keywords: Early Childhood; Covid-19; Learning Management; reference